Amplify-and-forward strategy with limited feedback in two-way relay channels - Sahin, Selami; Aygölü, Ümit (IEEE, 2011)
In physical-layer network coding (PLNC) for two-way relay channels (TWRC), consisted of one relay and two end nodes, implementation of amplify-and-forward (AF) strategy is difficult due to the need for full channel state information (CSI) about the two links at all nodes, which cause extra protocol complexity. In this paper, we introduce the limited feedback technique into the PLNC protocol utilizing AF strategy and propose a practical scheme in which the partial CSI is fed back to the end nodes from relay using limited number of feedback bits to inform about the other link. Upper bounds on the bit error probability depending on the number of feedback bits are derived for binary phase shift keying (BPSK) and quadrature-PSK (QPSK) modulations. It is shown via computer simulations that the error performance of the system with full CSI at all nodes are achieved by using a few number of feedback bits. Moreover, the computation complexity is reduced for the proposed scheme with single antenna at all nodes.